2021
DOI: 10.1002/ange.202110404
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+‐Coordination‐Driven RNA Assembly with Retained Integrity and Biological Functions

Abstract: Metal-coordination-directed biomolecule crosslinking in nature has been used for synthesizing various biopolymers,including DNA, peptides,proteins,and polysaccharides. However,the RNAbiopolymer has been avoided so far,asdue to the poor stability of the RNAm olecules,t he formation of ab iopolymer may alter the biological function of the molecules.H erein, for the first time,w er eport Zn 2+ -driven RNAs elf-assembly forming spherical nanoparticles while retaining the integrity and biological function of RNA. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It has been reported that the imidazole- and pyridine-type nitrogens of nucleotides in RNA were well suited for Zn 2+ binding. The phosphate unit and keto oxygen also have high affinity toward Zn 2+ to form chelate cross-links. , Therefore, we speculated that the competition between siRNA and 2-dimethylimidazole to coordinate with Zn 2+ ions decreased the efficiency of ZIF-8 crystal formation, thereby reducing the size of the NPs. These results indicated that the encapsulation of siRNA had a significant influence on the crystal structure of ZIF-8 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the imidazole- and pyridine-type nitrogens of nucleotides in RNA were well suited for Zn 2+ binding. The phosphate unit and keto oxygen also have high affinity toward Zn 2+ to form chelate cross-links. , Therefore, we speculated that the competition between siRNA and 2-dimethylimidazole to coordinate with Zn 2+ ions decreased the efficiency of ZIF-8 crystal formation, thereby reducing the size of the NPs. These results indicated that the encapsulation of siRNA had a significant influence on the crystal structure of ZIF-8 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Other candidates that are at the early stage in mRNA delivery potentially offer new opportunities in cancer immunotherapy, mainly including mesoporous silica nanoparticles with a high porosity [ 89 ], Zn 2+ ions [ 125 ], outer membrane vesicles (OMVs) derived from bacteria [ 24 ]. The advantages and disadvantages of representative types of mRNA delivery nanoparticles are summarized in Table 1 .…”
Section: Delivery Strategies For Mrna Therapeuticsmentioning
confidence: 99%
“…[11] To avoid these cationrelated side effects, non-electrostatic loading strategies driven by other interactions like base complementary pairing, [84][85][86] hydrogen bonding, [87] and coordination have been explored for mRNA delivery. [88,89] For example, forming metal/mRNA complex via metal coordination-mediated self-assembly is a practical strategy to condense mRNA. Zou et al applied Zn 2+ -directed mRNA selfassembly to prepare spherical NPs, which preserved the biological function of mRNA and achieved effective green fluorescent protein (GFP) expression, demonstrating the potential of metal coordination-driven mRNA self-assembly and broaden the application of mRNA-based therapeutics.…”
Section: Mrna Delivery Systemsmentioning
confidence: 99%
“…Zou et al applied Zn 2+ -directed mRNA selfassembly to prepare spherical NPs, which preserved the biological function of mRNA and achieved effective green fluorescent protein (GFP) expression, demonstrating the potential of metal coordination-driven mRNA self-assembly and broaden the application of mRNA-based therapeutics. [88] Various types of mRNA delivery systems have been developed, including lipid-based, polymer-based, nucleic acid-based, peptide-based, protein-based, cell-based, biological membranebased, and hybrid delivery systems (Figure 4). Of note, apart from mRNA itself, the mRNA delivery system also has impacts on the immunogenicity and inflammation of the final mRNA nanomedicines.…”
Section: Mrna Delivery Systemsmentioning
confidence: 99%